Resource Allocation Algorithm Modeling in Queuing System Based on Quantization; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Raspopov A. V. Aleksandr Vladimirovich (Information Technology, Data and Signal Processing, 2016)
Title screen